Disseminated phaeohyphomycosis with hepatic artery and portal vein thrombosis caused by Pleurostomophora richardsiae in a liver transplant recipient: A case report - Wantin Sribenjalux (2020)
© 2019 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd Pleurostomophora richardsiae is a dematiaceous mold that causes subcutaneous cystic phaeohyphomycosis. Few cases of invasive P richardsiae infection have been reported. Hepatic artery thrombosis following organ transplantation caused by a fungal organism is also very rare. We present here a 57-year-old man with refractory ascites and liver failure following liver transplantation for treatment of hepatocellular carcinoma. Abdominal computed tomography demonstrated total occlusion of hepatic artery and blood clot in the portal vein and inferior vena cava. P richardsiae was isolated from blood culture and the blood clot in his liver. The patient was treated successfully with a 4-week course of amphotericin B deoxycholate and liver retransplantation.